2011
DOI: 10.1016/j.adolescence.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Does family experience influence political beliefs? Relation between interparental conflict perceptions and political efficacy in late adolescence

Abstract: The study examined the relation between adolescents’ interparental conflict perceptions and their political efficacy regarding local issues. Longitudinal data (age 15 and 17) from 444 adolescents were analyzed using structural equation modeling. Results showed that young people experiencing frequent interparental conflict reported an increase in depressive mood during late adolescence, which was associated with lower level of political efficacy. Moreover, adolescents who felt more efficacious when dealing with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
14
0
1
Order By: Relevance
“…Here we adopt the notion commented on earlier that some aspects of family life have similar characteristics to participation in general. Cognitive schemata, formed in the family, are generalized and have an infl uence in other spheres, for example in community or political participation (Šerek, Lacinová & Macek, 2012). In fact adolescents' perceptions of their own leverage in issues aff ecting their communities, schools, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Here we adopt the notion commented on earlier that some aspects of family life have similar characteristics to participation in general. Cognitive schemata, formed in the family, are generalized and have an infl uence in other spheres, for example in community or political participation (Šerek, Lacinová & Macek, 2012). In fact adolescents' perceptions of their own leverage in issues aff ecting their communities, schools, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Strong family connections are associated with increased civic engagement (e.g., voting, volunteering, participating in social actions) (Duke, Skay, Pettingell, & Borowsky, 2009). Adolescents exposed to parental conflicts who feel that they cannot reduce home conflict levels subsequently experience depressive moods and lower political efficacy (Šerek, Lacinová, & Macek, 2013), suggesting that youths' experience in their immediate environment can affect how they feel about civil society more broadly.…”
Section: Parental Expectations and Supportmentioning
confidence: 99%
“…Other studies have concluded negatively about the possibility of Internet use enhancing PE. Serek and Macek () found that over a five‐month period of increased media consumption, including Internet use, PE levels did not change. Rather, they assert that the media consumption level depends on one's sense of PE.…”
Section: Political Efficacy and Internet Use: Literature Reviewmentioning
confidence: 99%
“…But one might argue that it is the concept of PE itself that is the problem: First, the definition of PE and the way in which PE is referenced is so diverse among the studies that its use for finding an answer to the above question is questionable. For example, some studies do not distinguish between IPE and EPE (Brunsting & Postmes, ; Quintelier & Vissers, ; Vitak et al, ); some refer to one of either of IPE or EPE as simply PE (Serek & Macek, ); others, while distinguishing between IPE and EPE, use PE throughout the text without clarifying which is being specified (Coleman et al, ; Sharoni, ). Since IPE and EPE differ in their characteristics (Balch, ; Craig & Maggiotto, ), a lack of such differentiation in the research hypotheses tends to invalidate the answers because it is not clear whether a different statistical outcome might result by specifying IPE or EPE.…”
Section: Political Efficacy and Internet Use: Literature Reviewmentioning
confidence: 99%